A Fundamental Study Of Oxygen-Melt Reactions In The AOD Process - G. S. Rao (The Minerals, Metals and Materials Society, 2006)
Levitated drops of Fe-18%Cr-2%C were reacted with oxygen-argon mixtures to study the reactions that occur in the AOD process, where the gases are injected into the melt and form bubbles. In the laboratory an argon-oxygen pulse, followed by pure argon, was flowed past the levitated drop to simulate the transient conditions in the gas phase as the bubbles rise in the melt. Oxide layers formed on the drops immediately when they came into contact with gas pulses containing 75% or more oxygen. Once the oxygen flow had ceased, the oxides reacted with the carbon in the drops to form CO gas and eventually disappeared. The de-carburization reaction occurred without oxide formation when the gas contained 50% oxygen or less. Melts that were sampled after EAF tapping, ready to be charged into the AOD, showed a higher tendency to oxide formation and consequent carbon boil than pure ternary Fe-18%Cr-2%C alloys made in the laboratory. The actual steel samples contained significant impurities, such as 0.25% Si and 0.56% Mn. A similar effect of oxide-forming impurities had been observed previously with binary Fe-C alloys. Movies were taken of the oxide formation and decomposition, and the results will be presented, along with data on the experimental conditions, including temperature and oxide compositions. The results are important because they give an insight into the reaction mechanisms in the AOD, which must be understood in order to improve and model the process.